Self-standing three-dimensional networks of nanoparticles with controllable morphology by dynamic templating of surfactant hexagonal domains - Sharma, Kamendra P.; Ganai, Anal Kumar; Sen Gupta, Sayam; Kumaraswamy, Guruswamy (Chemistry of Materials, 2011)
Assembly of nanoparticles into free-standing three-dimensional networks has implications for a wide range of applications. We show that dynamic templating of surfactant hexagonal domains is a facile technique to organize nanoparticles into a network of particulate strands. Dispersed particles (> 10 nm), independent of particle chemistry, assemble into networks, when the surfactant matrix cools into the hexagonal phase. We demonstrate assembly of inorganic, polymeric, and protein nanoparticles into networks. Where particle assembly is reversible, particles are coated with polymers that are subsequently cross-linked to stabilize the networks after surfactant removal. This technique involves near ambient temperatures and a benign water wash for template removal. The network mesh size can be varied from submicrometers to tens of micrometers by controlling the cooling rate. Particle networks can be flow-oriented prior to cross-linking, and interpenetrating networks can also be formed.
Keywords: hexagonal; macroporous; nanoparticle; self assembly; surfactant

Synthesis of functional hybrid silica scaffolds with controllable hierarchical porosity by dynamic templating - Ganai, Anal Kumar; Kumari, Sushma; Sharma, Kamendra P.; Panda, Chakadola; Kumaraswamy, Guruswamy; Sen Gupta, Sayam (Chemical Communications, 2012)
We report a facile one-pot synthesis of hierarchically porous scaffolds, with independent control over nanoparticle mesoporosity and scaffold macroporosity. Our technique combines the chemistry of mesoporous silica nanoparticles with the control afforded by dynamic templating of surfactant mesophases. These materials are readily functionalizable and allow controllable spatial variation in macroporosity.